2015
DOI: 10.1016/j.socnet.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of network structures of Wikipedia discussion pages on the efficiency of WikiProjects

Abstract: Publication informationSocial Networks, 43 : 1-15Publisher Elsevier Item record/more information http://hdl.handle.net/10197/9073 Publisher's statementThis is the author's version of a work that was accepted for publication in Social Networks. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
(46 reference statements)
2
20
0
Order By: Relevance
“…There have been exceptions to this limitation, and a few papers have compared community structures across projects. In this research, equality of participation and network density typically have a negative relationship with performance and community growth (D. Hinds & Lee, 2009;Qin, Cunningham, & Salter-Townshend, 2015;Roth, Taraborelli, & Gilbert, 2008).…”
Section: Communication Network In Commons-based Peer Productionmentioning
confidence: 86%
See 2 more Smart Citations
“…There have been exceptions to this limitation, and a few papers have compared community structures across projects. In this research, equality of participation and network density typically have a negative relationship with performance and community growth (D. Hinds & Lee, 2009;Qin, Cunningham, & Salter-Townshend, 2015;Roth, Taraborelli, & Gilbert, 2008).…”
Section: Communication Network In Commons-based Peer Productionmentioning
confidence: 86%
“…How might we expect coordination and social integration processes to occur in early-stage CBPP and what sorts of communication structures would reflect productive and long-lasting communities? The empirical evidence, primarily from lage-scale CBPP projects, suggests that dense communication networks are weakly, but negatively, associated with performance (Qin et al, 2015;Roth et al, 2008). While it is tempting to assume that these findings are common to all CBPP, there are a number of theoretical and empirical reasons to believe that early-stage projects have a different composition of members and different objectives than mature projects.…”
Section: Communication In Nascent Peer Production Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from Wikipedia collaboration has shown that, although old-timers have the experience and skills to contribute, their effort or motivation is generally lower than that of newcomers [41]. However, [25] showed that greater average membership tenure relates to project efficiency in a positive way. Our results do not show that experience, or tenure, in terms of the amount of time that an individual has been part of the Wikipedia community, has any effect on article quality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preexisting social capital, operationalized as the proportion of collaborators being members of a pre-existing network and the overall cohesiveness of a pre-existing network, increased the efficiency of collaboration among Wikipedia contributors [16]. A recent study further suggested that an intermediate level of cohesion in the collaboration network improved WikiProject efficiency [17].…”
Section: Related Workmentioning
confidence: 99%